2005
DOI: 10.1002/chem.200401289
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Glycoblotting Nanoparticles for High‐Throughput Protein Glycomics

Abstract: We have developed an effective and practical trap-and-release method based on chemoselective ligation of carbohydrates with reactive aminooxyl groups attached to the surface of nanoparticles (referred to as glycoblotting nanoparticles). These glycoblotting nanoparticles were synthesized by UV irradiation of diacetylene-functionalized lipids that contain the aminooxyl group. The glycoblotting nanoparticles captured carbohydrates in aqueous solution under mild conditions and were collected by simple centrifugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Our finding, however, indicates that the quantitative serum glycomic profile could be severely affected by the digestion condition used, and therefore care should be taken when handling the quantitative glycomics data. As an efficient tool to rapidly purify oligosaccharides from highly complicated biological matrices, we recently developed a chemoselective glycoblotting platform utilizing synthetic polymers displaying aminooxy functionality (31)(32)(33). The combination of the described standardized sugar-liberating protocol and glycoblotting technique for high throughput, large scale disease-related serum glycomics is currently in progress in our laboratory.…”
Section: Effect Of Pngase F Digestion Conditions On Efficiency Ofmentioning
confidence: 99%
“…Our finding, however, indicates that the quantitative serum glycomic profile could be severely affected by the digestion condition used, and therefore care should be taken when handling the quantitative glycomics data. As an efficient tool to rapidly purify oligosaccharides from highly complicated biological matrices, we recently developed a chemoselective glycoblotting platform utilizing synthetic polymers displaying aminooxy functionality (31)(32)(33). The combination of the described standardized sugar-liberating protocol and glycoblotting technique for high throughput, large scale disease-related serum glycomics is currently in progress in our laboratory.…”
Section: Effect Of Pngase F Digestion Conditions On Efficiency Ofmentioning
confidence: 99%
“…Because of its high ionization efficiency of aoWR on MALDI-TOF analysis, aoWR derivatives could be highly selectively detected with minimum purification steps. We have recently reported that polymers displaying oxylamino groups provide a useful platform for "glycoblotting," a high throughput oligosaccharide purification procedure in a crude mixture (22,23). Derivatization with aoWR is therefore regarded as an analogue of glycoblotting where chemoselective ligation is done using functional low molecular weight compounds instead of polymers.…”
Section: Table I Observed Signals Of Aowr-labeled Oligosaccharides Rementioning
confidence: 99%
“…Our recent efforts have been directed to the establishment of practical methods for glycan enrichment, namely "glycoblotting" (15)(16)(17)(18)(19)(20). The optimized protocol requires only 5 l of human serum for the quantitative profiling of 30 -40 kinds of major glycoforms within 5-8 h (19).…”
mentioning
confidence: 99%